Structural Color Tuning Mixing Melanin-Like Particles with Different Diameters to Create Neutral Colors - Kawamura, Ayaka (Langmuir : the ACS journal of surfaces and colloids, 2017)
We present the ability to tune structural colors by mixing colloidal particles. To produce high-visibility structural colors, melanin-like core-shell particles composed of a polystyrene (PSt) core and a polydopamine (PDA) shell, were used as components. The results indicated that neutral structural colors could be successfully obtained by simply mixing two differently sized melanin-like PStPDA core-shell particles. In addition, the arrangements of the particles, which were important factors when forming structural colors, were investigated by mathematical processing using a 2D Fourier transform technique and Voronoi diagrams. These findings provide new insights for the development of structural color-based ink applications